Answer:
x-2y/x
Step-by-step explanation:
x²-4xy+4y²/x²+xy-6y²÷x²+3xy/x²+6xy+9y² = x-2y/x
Answer:
Step-by-step explanation:
Step-1 : Multiply the coefficient of the first term by the constant 2 • 2 = 4
Step-2 : Find two factors of 4 whose sum equals the coefficient of the middle term, which is 3 .
-4 + -1 = -5
-2 + -2 = -4
-1 + -4 = -5
1 + 4 = 5
2 + 2 = 4
4 + 1 = 5
Observation : No two such factors can be found !!
1, 3, 9 and -1, -3, and -9 i guess
hope this helps
Answer:
first one is a and the second one is c